Perubahan Interaksi Konsumen dan Pedagang Pasar Tradisional pada Era Digital - Azizatul Fitriyah; Rizki Febri Eka Pradani (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Digitalization has brought significant transformations to the interaction patterns between consumers and traditional market merchants, triggering a shift from conventional face-to-face meetings toward a combination of direct and digital-based communication such as social media and instant messaging applications. This phenomenon in Sukosari Market, Bondowoso demonstrates that technology utilization accelerates the processes of promotion, communication, and non-cash transactions, thereby increasing trade efficiency without eliminating the core social values that characterize traditional markets. Through a descriptive qualitative approach, it is revealed that merchants adapt by utilizing digital devices to retain customers, while consumers benefit from flexible access to price information and stock availability. Nevertheless, challenges such as low digital literacy and limited technological devices are still faced by some senior merchants. Personal relationships, emotional closeness, and the bargaining tradition are maintained as foundations that preserve the existence of traditional markets amidst the currents of modernization. The integration between digital technological advancements and social relationships proves that digitalization is not merely a substitute, but a complementary means that reinforces the sustainability of modern economic interaction spaces.